The Role of Learning Behaviors in Explaining the Relationship between Employee Orientation and the Performance of Banking Service Recoveries (Analytical Study). - Dawas, Bashaur Saad (International Journal of Psychosocial Rehabilitation, 2020)
The present study aims to explore the relationship between employee orientation and the performance of banking service recoveries throughout the mediator role of learning behaviors from a sample of workers in governmental banks in Al-Muthanna Governorate (Al-Rashid Bank, Al-Rafidain Bank, the Real Estate Bank, and the Agricultural Bank). In addition, the sample of the present study was 137 workers with differences in their academic achievement and manageable positions. This research has been conducted based on major hypotheses that are branched into other hypotheses. The study has used to test the hypotheses, which is based on a set of suitable statistical tools represented by confirmatory factor analysis and structural modeling equation. The findings showed a set of conclusions and recommendations, one of the most important which was exploring the relationship between employee orientation and banking service recoveries, as it has a great importance not only because of its importance in the competitive advantage issues but also to help other workers to find solution to keep the new and existing customers. Hence, keeping the existing customers represents one of the major factors.